Evolution: medicine's missing basic science - Nesse, Randolph (Henry Stewart Talks, 2007)
How evolution is useful to medicine, Why doctors don't know evolution, The body: perfect and pathetically flawed, Proximate and evolutionary explanations, Explain vulnerability, not diseases, Six reasons for vulnerability, Darwinian medicine growing fast
Archived at 2023/06/22